2022
DOI: 10.3390/brainsci12121660
|View full text |Cite
|
Sign up to set email alerts
|

Carob Seed Peels Effect on Cognitive Impairment and Oxidative Stress Status in Methionine-Induced Mice Models of Schizophrenia

Abstract: Ceratonia siliqua L. (Carob tree) is a Mediterranean evergreen, well known for its medicinal properties. The different parts of Carob were proven to exert antidiabetic, antibacterial, antifungal, and antiproliferative effects. Hence, the present paper aims to validate the positive correlation between the high antioxidant activity of carob seed peels and the improvement of negative symptoms of schizophrenia. Materials & Methods: The antioxidant activity was carried out using the β-carotene test. Methionine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…C. siliqua pods are known for their antioxidant properties that are of value for the amelioration and prevention of many disorders [ 33 , 34 ]. In the literature, there are many studies comparing different extraction methods to prepare an active extract.…”
Section: Discussionmentioning
confidence: 99%
“…C. siliqua pods are known for their antioxidant properties that are of value for the amelioration and prevention of many disorders [ 33 , 34 ]. In the literature, there are many studies comparing different extraction methods to prepare an active extract.…”
Section: Discussionmentioning
confidence: 99%
“…In general, under hypoxic conditions, the percentage of GSH stimulation was higher compared to normoxic ones, most probably due to the fact that hypoxia minimized basal GSH levels, as previously shown in various cell types [69,70]. Although there are several reports on the beneficial effects of various carob extracts on the GSH levels in whole organisms, mainly as part of their antioxidant defenses and during detoxification processes [71][72][73][74], this is the first study showing that C. siliqua extracts stimulate GSH at the cellular level.…”
Section: Discussionmentioning
confidence: 66%
“…Te potential health benefts of carob seed peels were studies by Lakkab et al [26,29] and Rico et al [27], who confrmed their remarkable antioxidant properties. Te studies conducted by these researchers brought to light the richness of bioactive compounds.…”
Section: Medicinal Efect Of Carob Seed Peel Compoundsmentioning
confidence: 99%
“…According to the research carried out by Lakkab et al [29], it was discovered that CSP demonstrated a markedly greater accumulation of total phenolic content, amounting to 9573 ± 1 mg GAE/100 g extract in contrast to other by-products, such as potato peel which only registered 68.7 ± 5.7 mg GAE/100 g dry weight [30] and carob pulp (4.53 ± 0.8 mg/100 g of dry matter) [10], which are typically recommended for similar benefciation procedures. CSP also demonstrated the greatest ability to inhibit the discoloration of β-carotene compared to BHT (58.3% versus 46%) [29]. Tis was explained by high content of phenolic compounds.…”
Section: Total Phenolic Levels (Tpl) and Radical-scavenging Capabilit...mentioning
confidence: 99%